The Impact of Personality Types on Students’ Speaking Ability : A Quasi-Experimental Study - Hermi Zaswita (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Personality can be one of the internal factors that have an impact on students’ ability in language learning. The present study investigated the impact of personality types on their ability in writing English. There are two types of personalities studied: Extrovert and Introvert. The research is quasi-experiment. Students at grade XI SMAN 6 Kerinci engage in the study, whereas only two classes selected as samples (experimental class and control class). Students were given a personality questionnaire to recognize their personality types. Then, the speaking test carries out in each class in order to know the student's ability in writing. The data are analysed by using t-test. The finding of hypotheses testing proves that the value of t-observed is 19.43 which is higher than t-table 4.301, so H0 is rejected and H1 is accepted. Hence, there is a significant impact on students’ personalities to their speaking ability. Students with extrovert personalities have better speaking than students with introvert personality.